Application of Ribosomal Internal Transcribed Spacer 1, Internal Transcribed Spacer 2, and Large-Subunit D1–D2 Regions as the Genetic Markers to Identify Fungi Isolated from Different Environmental Samples: A Molecular Surveillance Study of Public Health Importance. (2nd April 2020) - Sulaiman, Irshad M; Jacobs, Emily; Simpson, Steven
Abstract: Background: In September 2012, a multistate fungal meningitis outbreak started across 20 states in the United States. It affected 753 individuals and caused 64 deaths who received contaminated spinal injections. In a previous study, we analyzed 26 environmental samples collected from the manufacturing premises of a compounding company to determine the possible cause of an outbreak and identified 14 distinct fungal species. Objectives: In this follow-up study, we have analyzed 198 environmental samples collected from three additional compounding company premises located in the United States for the presence of pathogenic fungi. Methods: Environmental swab samples were initially examined by standard microbiological methods. Subsequently, DNA sequencing was performed on all of the 25 recovered fungal isolates at the D1–D2 domain of the large subunit (LSU) ribosomal RNA (rRNA) and the internal transcribed spacer (ITS) regions. Results: Sequence analysis of the ITS1, ITS2, and LSU rRNA regions confirmed the presence of the following fungal species in the environmental samples analyzed: (i) Pestalotiopsis cocculi from the region Ia; (ii) Epicoccum nigrum and Trichaptum biforme from the region Ib; (iii) Nigrospora sphaerica and Fusarium sp. from the region II; and (iv) Curvularia sp., Fusarium sp., Penicillium sp., and Preussia sp. from the region III. Species identification of 25 recovered fungal isolates matched, in most cases, at 3 sequenced loci (ITS1, ITS2, and LSU). Highlights: DNA sequencing of ITS1, ITS2, and LSU D1–D2 regions can be used to perform fungal typing and in implementing effective environmental monitoring programs of public health importance.